The chicken who saved us : the remarkable story of Andrew and Frightful - Adams, Kristin Jarvis (Behler Publications, 2017)
"Young Andrew was autistic and bilingual. He spoke English-and Chicken. He would sit on the front porch deep in conversation with his best friend, an Araucana chicken named Frightful. It was a two-way dialog consisting of secrets told and secrets kept between boy and fowl. His feathery friend became his voice; his only way to communicate in a confusing world. But one day, Andrew confided to Frightful: 'I think my body is trying to kill me.' That single statement catapulted Andrew's family and medical community into action: To discover and destroy the unseen monster that was claiming Andrew's life--a disease that created pain so great that no painkiller could touch it. By the time Andrew was sixteen, he had spent seven years in and out of the hospital. Through it all, Frightful listened as she sat in his lap or zoomed down the street on his new electric bike, stuffed into his jacket, zippered up to her beak. Hospitalized, Andrew talked to Frightful with the aid of two iPads and a FaceTime connection. Her love and friendship armed Andrew with the courage of a superhero as he received an experimental bone marrow transplant. He wasn't expected to live through the night, but he shouted into a room full of doctors, nurses, and family, 'Bring It On!' At his graduation, Andrew stood in front of an auditorium of parents, administrators, and peers and delivered a speech titled 'Why I Think Chickens Have Autism.' He received a standing ovation"--